Implementasi media pembelajaran factomat pada materi persamaan kuadrat untuk mendukung pemahaman konsep siswa kelas x man kota mojokerto - Mukhlisoh, Yeni (Maliki Interdisciplinary Journal, 2025)
Understanding mathematical concepts, particularly quadratic equations, remains a challenge for many students. This study aims to determine the effectiveness of Factomat learning media in improving conceptual understanding for tenth-grade students. Factomat media is an interactive visual sheet that guides students in understanding the factorization of quadratic equations until they find their roots. The main instrument is a descriptive test given after the learning process. The results show an increase in average scores, with the majority of students achieving the minimum completion criteria and being in the good to very good understanding category. These findings indicate that Factomat media is effective in improving understanding of mathematical concepts and providing a fun and structured learning experience. This media has the potential to be an effective alternative in supporting mathematics learning in secondary schools.